PENGARUH PENERAPAN SISTEM E-BILLING, E-FILLING DAN E-FAKTUR TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Ashapira Faujiyah; Dwi Septiani (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This research discusses the Influence of the Implementation of E-Billing, E-Filling and E-Faktur Systems on Individual Taxpayer Compliance at the Pondok Aren Pratama Tax Service Office. This study aims to test the influence of the implementation of e-billing, e-filling and e-faktur systems on individual taxpayer compliance. This type of research is quantitative research. The population in this study were individual taxpayers in the city of South Tangerang consisting of 446.397 taxpayers. A sample of 400 taxpayers was taken. Data analysis techniques are descriptive statistics, data quality testing, hypothesis testing using SPSS V25. The results of the study indicate that the influence of the implementation of e-billing, e-filling and e-faktur systems simultaneously influences individual taxpayer compliance. Partially, the implementation of e-billing, e-filling and e-faktur systems has a positive and significant effect on individual taxpayer compliance.